EVALUASI KINERJA BIAYA DAN WAKTU PELAKSANAAN MENGGUNAKAN METODE EARNED VALUE (EVM) (Studi Kasus: Proyek Pengendalian Banjir Kali Lamong) - Annas, Ferry Muhammad; Solikin, Mochamad; Harnaeni, Senja Rum; Sunarjono, Sri (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The Kali Lamong Project is scheduled to be completed within 35 weeks with acontract value of Rp. 72,000,000,000,-. The purpose of this study is to determinecost and time performance, cost and time estimates at the end of project completionand the factors that cause delays or project progress. The method used in this studyis the Earned Value method which combines the elements of cost and time as well asthe physical performance of the work The data obtained from the project includesthe project time schedule, budget plan (RAB), project weekly reports and actualcosts, then an analysis of costs, schedules, variances and performance indexes iscarried out by explaining the problems that arise during the research. From theresults of the analysis it is known that the costs incurred are lower than thebudgeted costs indicated by the value of CPI = 1.12 and the implementation time isslower than the planned schedule indicated by the value of SPI = 0.71. The resultsof the calculation of the estimated final project cost of Rp. 67,952,500,564.98 withan estimated completion time of 43 weeks, indicating that the project experienced adelay of 8 weeks from the planned 35 weeks. This delay was caused by variousfactors such as delays in the initial erection of the project by a third party, damageto equipment, changes to the drawings by the planning consultant and changes tothe design by the owner.